Oral health literacy and oral health status among undergraduate University students / Azlan Jaafar, Normaliza AB Malik and Aws Hashim Ali AL-Kadhim - Jaafar, Azlan; AB Malik, Normaliza; AL-Kadhim, Aws Hashim Ali (Faculty of Medicine, 2021)
Introduction: To identify the prevalence of caries, plaque score, and periodontal disease and explore the correlations between oral health literacy scores and oral health status among undergraduate students. Methods: A cross-sectional study was conducted with a group of undergraduate students using the Malay version of the Oral Health Literacy (OHL) Index. A stratified random sampling technique was used to select the samples. Clinical oral examinations were conducted by a single trained examiner using a Community Periodontal Index (CPI) probe and a mouth mirror. Data analysis was conducted using statistical tests contained in SPSS version 26, and statistical significance was set at p<0.05. Results: A total of 280 students were recruited into the study. The prevalence of caries and periodontal disease was 58.9 and 13.2%, respectively. There was a significant association between OHL and field of study (p<0.001). There was also a significant negative but weak correlation between OHL and dental plaque scores (r= -0.147; p=0.014). A significant positive but weak correlation was found between dental plaque scores and dental caries (r= 0.135; p=0.024) and periodontal pocket depth (r= 0.168; p=0.005). Conclusion: The prevalence of dental caries was high, while the prevalence of periodontal diseases was low in this study. OHL correlated significantly with dental plaque scores and field of the study. Thus, OHL assessment is essential to understand a person’s OHL levels and can be considered a screening tool for early detection of poor oral hygiene.